Narcissim, gratitude, and general well-being on relationship satisfaction among married couples in Malaysia - Chuah, Zi Ling; Lee, Mei Kei; Tan, Sym Yee (2022)
Relationship satisfaction evaluates and assesses a person's qualitative interpretation of a relationship's quality. Nowadays, relationship satisfaction may have been changed by many issues such as narcissist personality, gratitude, and general well-being. It is worthful research to investigate the relationship between relationship satisfaction and these three predictors (narcissism, gratitude, and general well-being) among married couples in Malaysia. A quantitative study design through the snowball sampling method was used in the current study. Pearson’s Product Moment Correlation (PPMC) and Multiple Linear Regression (MLR) were used to analysis this research. The instruments used in this study are Hypersensitive Narcissism Scale (HSNS), Gratitude Questionnaire-Six Item Form (GQ-6), 18-item General Well-Being Schedule and Relationship Assessment Scale (RAS). Qualtrics was used to create the questionnaire, and it was posted on different social media, such as Facebook, WhatsApp, Instagram, and so on. 100 married individuals (44 males and 56 females) participated in this research. The age range for these respondents is between 21 to 60 years old (mean=36.68). The result showed that gratitude and general well-being were positively and significantly predicted the relationship satisfaction among married couples in Malaysia. However, narcissism was positively and non-significantly predicted the relationship satisfaction. This study may help to raise awareness about healthy relationships among different kinds of couples. This study able to help raising the awareness of healthy relationship and the information applicable in gratitude therapy. This research study provides an implication to the professionals to get advice in dealing with marriage problem.